2018
DOI: 10.1007/s10072-018-3286-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between serum vitamin B12 deficiency and tension-type headache in Turkish children

Abstract: This study aimed to determine the relationship between serum vitamin B level and tension-type headache. The study groups consisted of 75 patients (40 females, 35 males) with headache and a control group of 49 healthy children (25 females, 24 males). Serum vitamin B level < 200 pg/ml was defined as deficient, and < 160 pg/ml as severely deficient. The serum vitamin B level was measured by the electrochemiluminescence (ECLIA) method. The serum vitamin B levels in the headache and control groups were 273.01 ± 76.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
0
18
0
2
Order By: Relevance
“…Preliminary studies have found an association between vitamin deficiencies and headaches, but large studies on the topic are lacking. 22,23 When examining potential effect modification by gender, we did not observe a statistically significant difference between ORs for number of ACEs and headaches in females and males. The results from observational studies conducted in adults have shown gender differences in the association between headache and ACEs.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Preliminary studies have found an association between vitamin deficiencies and headaches, but large studies on the topic are lacking. 22,23 When examining potential effect modification by gender, we did not observe a statistically significant difference between ORs for number of ACEs and headaches in females and males. The results from observational studies conducted in adults have shown gender differences in the association between headache and ACEs.…”
Section: Discussionmentioning
confidence: 63%
“…For example, children lacking proper nutrition resulting from limited family financial resources may be at increased risk of headaches. Preliminary studies have found an association between vitamin deficiencies and headaches, but large studies on the topic are lacking …”
Section: Discussionmentioning
confidence: 99%
“…In this pathway, Hcy is produced as an intermediate substance and it is removed by remethylation to methionine in the presence of vitamin B12 and folate. 19 However, it should be noted that the comparability of this study with the present one is limited according to the inclusion criteria of the age groups and the respective investigation of a different type of headache. 13,14 Therefore, in addition to vitamin B12, vitamins B6 and B9 also could play a substantial role in lowering the level of homocysteine and subsequently in alleviating migraine headaches.…”
Section: Discussionmentioning
confidence: 86%
“…[52][53][54] Thus, the lack of these vitamins, especially B12, and consequently disturbance in biosynthesis of methionine lead to an elevated total Hcy (hyperhomocysteinemia) level. 19 According to the previous studies on the relationship between thrombotic events and migraine, especially migraine with aura, this type of primary headache has been identified as a risk factor for cardiovascular events, through a variety of pathophysiological processes. 14,41 This hypothesis can be further supported by a few clinical trials that have shown the positive effects of a combination of vitamin B groups including B6, B9, and B12 on migraine characteristics especially through reducing Hcy serum concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation